Digital Transformation and Technostress: Design-Oriented Solutions - Taşkın, Nuri (Information World, 2025)
This study aims to examine the book titled “Digital Transformation and Technostress: Design-Oriented Solutions.” The book was published as a derivative of the doctoral dissertation titled “User-Compatible Digital Transformation Processes, Technostress, and Design-Oriented Thinking Strategies in Information Services,” completed by Kaan Çınar in 2024. This book, consisting of four chapters, addresses topics such as user-compatible digital transformation, technostress, and the design-oriented thinking approach in information services. The book explores how design-oriented thinking approaches can be implemented in the field of information and documentation management, the technostress issues faced by users, and comprehensive solution proposals for these problems. Through this book, researchers have the opportunity to gain insights into current topics such as user-compatible digital transformation, technostress, and design-oriented thinking in information services.